2004
DOI: 10.1097/01.brs.0000143170.47345.44
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Repeated Radiofrequency Neurotomy for Lumbar Facet Pain

Abstract: Repeated radiofrequency neurotomies are an effective long-term palliative management of lumbar facet pain. Each radiofrequency neurotomy had a mean duration of relief of 10.5 months and was successful more than 85% of the time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 13 publications
9
73
0
5
Order By: Relevance
“…Moreover, its analgesic effect can be reinstated by repeating the procedure. 63,64,67,80 CRF is an effective treatment for the pain of facet joint and sacroiliac joint origin. Some technically incorrect RCTs discredited CRF in the treatment of facet arthropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, its analgesic effect can be reinstated by repeating the procedure. 63,64,67,80 CRF is an effective treatment for the pain of facet joint and sacroiliac joint origin. Some technically incorrect RCTs discredited CRF in the treatment of facet arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pain relief may be reinstated with similar duration and success by repeating the procedure. 80 …”
Section: Lumbar Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…При їх ефективності (зменшення чи регрес больового синдрому) виконується лікувальна денервація цих суглобів. Частина дослідників при наявності у пацієн-тів клінічної картини некомпресійних синдромів виконують денервацію фасеткових суглобів відразу, ґрунтуючись на тому фактові, що близько 30 % результатів після лікуваль-но-діагностичних блокад є хибнопозитивними [3,4].…”
unclassified
“…Schofferman et al 10) reported results of repeated radiofrequency neurotomy that showed a mean duration of relief of 10.5 months and more than 85% of successful rate in 20 patients. In this study, we included 60 patients who have undergone repeated RF medial branch neurotomy with modified technique and compared with previous results to determine the success rate and duration of pain relief.…”
Section: Introductionmentioning
confidence: 99%